Функционирование неологизмов и окказионализмов из сферы информатики и интернет-коммуникации в современном украинском языке - Кислюк, Лариса (Forum Lingwistyczne, 2020)
This paper is devoted to the analysis of term generation in the field of computer science and i-net communication using the native word-formative tools of the Ukrainian language. Particular attention is paid to the functioning of such neologisms in common usage (linguistic usus). Ukrainian electronic resources are used as a research material and verification tool. Morphemic, word-formative and comparative analysis of derivatives and the method of periphrasis allowed us to determine the reasons for the production of appropriate and inappropriate special names that can compete with English borrowings in this field.